1984
DOI: 10.1111/j.1471-0528.1984.tb05901.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine effects of danazol in the treatment of endometriosis

Abstract: summary The effects of danazol therapy on circulating gonadotrophins, oestradiol and sex hormone‐binding globulin (SHBG) binding capacity have been studied in eight patients with endometriosis. There was a significant rise in luteinizing hormone (LH) in the first week of treatment with a fall in oestradiol levels. There was a marked fall in SHBG in the first week which continued up to 4 weeks. It is concluded that danazol is not ‘antigonadotrophic’ as frequently claimed and that its therapeutic actions, side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…We have confirmed that administration of dana¬ zol is associated with a decrease in the serum con¬ centration of SHBG (21), probably due to inhibi¬ tion of hepatic synthesis of SHBG (22), and thus with a modest rise in the calculated free testoste¬ rone index. In vitro, testosterone stimulates (23), whereas insulin inhibits (24) the synthesis of SHBG.…”
Section: Discussionsupporting
confidence: 74%
“…We have confirmed that administration of dana¬ zol is associated with a decrease in the serum con¬ centration of SHBG (21), probably due to inhibi¬ tion of hepatic synthesis of SHBG (22), and thus with a modest rise in the calculated free testoste¬ rone index. In vitro, testosterone stimulates (23), whereas insulin inhibits (24) the synthesis of SHBG.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, it has been speculated that the therapeutic effect of danazol upon ectopic endometrium derives from the increased free androgen levels rather than from any antigonadotrophic action (Bevan et al 1984). Nonetheless, significant problems are apparent that make it unlikely they will replace existing contraceptive methods in most women.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Danazol, the 2 , 3 -~ isoxazol derivative of 17a-ethinyl testosterone (ethisterone), is widely used in the treatment of endometriosis on the basis of its supposed inhibition of gonadotrophin secretion (Sherins et al, 1971). Whilst it is well established that high dosages (above 400 mg per day) can suppress the mid-cycle LH surge and lead to cessation of menses, basal levels of LH and FSH are essentially unchanged in humans with intact gonadal function (Barbieri & Ryan, 1981;Bevan et al, 1984). Lower dosages ( c 200 mg per day) in most cases do not suppress cyclic menstruation but are nonetheless therapeutically effective (Biberoglu & Behrman, 198 1;Samaras et al, 1983).…”
mentioning
confidence: 99%
“…We have previously suggested that the androgenic activity of danazol in v i m may be at least partly dependent on its suppression of plasma sex hormone binding globulin (SHBG) levels (Bevan et al, 1984) which would be expected to result in an increase in the free, biologically active testosterone concentration. We have further confirmed that the percent free testosterone is significantly increased by danazol treatment (Dowsett et al, 19861, but total testosterone concentrations have been reported as decreased by some authors (Nilsson et al, 1983;Carlstrom et al.…”
mentioning
confidence: 99%